Correction: Folic acid-functionalized up-conversion nanoparticles: toxicity studies in vivo and in vitro and targeted imaging applications. Issue 36 (12th September 2017) - Sun, Lining; Wei, Zuwu; Chen, Haige; Liu, Jinliang; Guo, Jianjian; Cao, Ming; Wen, Tieqiao; Shi, Liyi
Abstract : Correction for 'Folic acid-functionalized up-conversion nanoparticles: toxicity studies in vivo and in vitro and targeted imaging applications' by Lining Sun et al., Nanoscale, 2014, 6, 8878–8883.